Analisis Laporan Arus Kas Untuk Menilai Kinerja Keuangan Pada KSP Pintu Air Cabang Akkareso Makassar - Mariana Oba Penu; Mardiana Ibrahim; Andi Bintang Balele (Universitas 17 Agustus 1945 Semarang, 2022)
The purpose of this research is to analyze and prove the effect of cash flow reports to assess financial performance at the Pintu Air Savings and Loans Cooperative, Akkareso Makassar Branch. The type of data used in this research is quantitative data, namely data that is a collection of numerical data. The research results show that cash flow in 2019 was obtained at a value of 29,409,800 and in 2020 it obtained a value of 28,115,300. In 2021 it produces a value of 39,201,500, an increase of 139.28% from 2020. The results of the liquidity ratio, namely the current ratio, in 2019 obtained a value of 201.26%, in 2020 it obtained a value of 212.70%, in 2021 it produced a value of 213 .00%, while the cash ratio in 2019 was 28.16%, in 2020 it was 22.51%. In 2021 it produces a value of 25.59%. For the profitability ratio, namely ROE in 2019, it obtained a value of 45.25%, in 2020 it obtained a value of 26.10%. In 2021 it produces a value of 19.89%. Meanwhile, in 2019 ROE was obtained at a value of 46.99%, in 2020 it obtained a value of 22.88%. In 2021 it produces a value of 19.12%.